The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acssuschemeng.9b05251
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Pressure-Swing Distillation toward Sustainable Process of Novel Continuous Ultra-High-Purity Electronic-Grade Propylene Glycol Monomethyl Ether Acetate Manufacture

Abstract: Ultra-high-purity propylene glycol monomethyl ether acetate (PGMEA) is required as an electronic-grade solvent to meet the stringent requirements of the rapidly developing semiconductor industry. The high demand for ultra-high-purity PGMEA has created the need for an efficient sustainable process for reducing energy consumption as well as satisfying tight waste management regulations. Here, a potentially sustainable and novel process for efficient continuous electronic-grade PGMEA manufacturing is presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…PGMEA is one of the most important solvents for photoresist processing in the semiconductor industry. It has relatively low environmental toxicity but all of the reactants required in its manufacture are from non-renewable sources [ 151 ]. Carcinogens used in photoresists (PR) products include cyclohexanone, ethylbenzene, pyridine, and 1,4 dioxane [ 34 ].…”
Section: Bottom-up Versus Top-down Lithographymentioning
confidence: 99%
“…PGMEA is one of the most important solvents for photoresist processing in the semiconductor industry. It has relatively low environmental toxicity but all of the reactants required in its manufacture are from non-renewable sources [ 151 ]. Carcinogens used in photoresists (PR) products include cyclohexanone, ethylbenzene, pyridine, and 1,4 dioxane [ 34 ].…”
Section: Bottom-up Versus Top-down Lithographymentioning
confidence: 99%
“…Recently, an attempt toward a sustainable process of continuous PGMEA production was reported [7]. First, a base-catalyzed reaction between propylene oxide (PO) and methanol (MeOH) was used to synthesize PGME.…”
Section: Introductionmentioning
confidence: 99%
“…At the top RD product, the more volatile mixture, MeAc and MeOH, as a binary azeotrope, was introduced into the low pressure distillation column section. Figure 1 presents a schematic diagram of the novel PGMEA production process [7]. That study showed that intensified RD and pressure swing distillation (PSD) techniques could increase the PGMEA conversion; thus, the energy requirement was significantly decreased compared to that of the traditional process [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations